PENGARUH PERUBAHAN METODE PENGUMPANAN SAMPAH BUAH PADA PRODUKSI GAS METAN TERHADAP STRUKTUR KOMUNITAS BAKTERI - INDRA K., YENI ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The increased of fruit waste such as oranges, apples, and melons can be minimized by using the waste as biogas production. Previous studies optimized from biodigester with the variation of feeding methods and fruit waste concentrations to determine the methane production. The purpose of this study was to determine the relationship between the feeding method with the bacterial community structure in methane biodigester, as well as between bacterial community structure with the methane production. This study used 5 types of samples taken from biodigesters in previous studies such as sample 1, which is the method of feeding with a composition of 35% fruit waste and 65% cow dung